From a Monster to a Dream Lover. On the Changing Cultural Image of the Vampire - Darska, Bernadetta (Media - Culture - Social Communication, 2019)
In the article titled From a Monster to a Dream Lover. On the Changing Cultural Image of the Vampire the author takes a look at the changing image of the vampire. Of particular interest to her is documenting the transformation from a character inspiring horror to a person who becomes a friend and a dream life partner. The tendency to inscribe vampires into everyday life and make them its ordinary part constitutes a perfect example of, on the one hand, embracing fears by the contemporary world and, on the other, turning all things dark and disturbing into banality